Phantom limbs: pain, embodiment, and scientific advances in integrative therapies. Issue 2 (11th February 2014) - Lenggenhager, Bigna; Arnold, Carolyn A.; Giummarra, Melita J.
<x xml:space="preserve">Abstract</x> Research over the past two decades has begun to identify some of the key mechanisms underlying phantom limb pain and sensations; however, this continues to be a clinically challenging condition to manage. Treatment of phantom pain, like all chronic pain conditions, demands a holistic approach that takes into consideration peripheral, spinal, and central neuroplastic mechanisms. In this review, we focus on nonpharmacological treatments tailored to reverse the maladaptive neuroplasticity associated with phantom pain. Recent scientific advances emerging from interdisciplinary research between neuroscience, virtual reality, robotics, and prosthetics show the greatest promise for alternative embodiment and maintaining the integrity of the multifaceted representation of the body in the brain. Importantly, these advances have been found to prevent and reduce phantom limb pain. In particular, therapies that involve sensory and/or motor retraining, most naturally through the use of integrative prosthetic devices, as well as peripheral (e.g., transcutaneous electrical nerve stimulation) or central (e.g., transcranial magnetic stimulation or deep brain stimulation) stimulation techniques, have been found to both restore the neural representation of the missing limb and to reduce the intensity of phantom pain. While the evidence for the efficacy of these therapies is mounting, but well‐controlled and large‐scale studies are still needed. WIREs Cogn Sci 2014, 5:221–231. doi: 10.1002/wcs.1277 Conflict of interest: The authors have no financial or other relationship that might lead to a conflict of interest. For further resources related to this article, please visit the WIREs website.